Supported imidazolium-based ionic liquid membranes as a Contactor for the selective absorption of CO2 by aqueous monoethanolamine / Nurul Ain Ramli - Nurul Ain , Ramli (2019)
Carbon dioxide (CO2) capture using supported ionic liquid membranes has been receiving a lot of attention in the past few years. The use of supported ionic liquid membranes and solvents that possesses good selectivity of capturing CO2 from flue gases has the potential to replace conventional absorption method. However, common good solvents for CO2 capture will extensively undergo degradation due to the presence of oxygen. Therefore in this work, novel technology of supported ionic liquids membranes (SILMs) is therefore used as contactor for the selective absorption of CO2 by aqueous monoethanolamine (MEA). First, a series of ILs were screened using COSMO-RS. For this purpose, CO2 absorption capacity and CO2/O2 selectivity of some selected ILs was predicted using this molecular modelling system. Results from the analysis revealed that [emim] [NTf2] IL was a good candidate for further absorption process, due to its good characteristics in its moderate hydrophobicity and CO2/O2 selectivity. Next, the role of viscosity in preparation of a new supported ionic liquid membrane (SILM) and its chemical stability were investigated. The maximum amount of ionic liquid immobilized within the membranes was acquired at [emim] [NTf2] IL: acetone; (80:20) composition. At this composition, the IL was also found to be homogeneously distributed. Based on the above results, the SILMs were found to be more stable in aqueous solution of MEA. This stability was corresponding with results of the ionic liquid losses obtained by mass balance. Subsequently, the CO2 absorption performance and CO2/O2 selectivity of the SILM and its performance with that of the blank membrane; were evaluated and compared at different temperatures (303 to 348 K) and gas velocities (4.63 x 10-6 to 3.70 x 10-5 m s-1). At pseudo-steady-state and long-term operation conditions, results showed that the efficiency of the CO2 absorption process of SILMs had almost doubled with an average selectivity factor of CO2/O2 around 5 times, as compared to the blank contactor system. In addition, the mass transfer coefficient using SILMs was found to be 3.3 times higher as compared to the blank system. Finally, the effect of important operating conditions on CO2 absorption performance and CO2/O2 selectivity of the supported ionic liquid membrane (SILM) were investigated. Higher value of the overall mass transfer coefficient of 3.83 x 10-5 ms-1 was obtained at optimal operating conditions, with a measured CO2/O2 selectivity of 140. In conclusion, results in this work ultimately suggests the promising potentials of [emim] [NTf2]-SILMs for further evaluation work; especially for the prevention of oxidative degradation of the amine solvents in membrane contactors applications for CO2 capture. Keywords: